Synthesis and mixed integer programming based optimization of cryogenic packed bed pipeline network for purification of natural gas. (10th January 2018) - Ali, Abulhassan; Maqsood, Khuram; Shin, Lam Pei; Sellappah, Varsheta; Garg, Sahil; Shariff, Azmi B.M.; Ganguly, Saibal
Abstract: The variation of temperature, pressure and composition during cryogenic purification of natural gas using cryogenic packed bed network significantly affects separation. The present work aims to optimize cryogenic packed bed network for maximum product purity with minimum hydrocarbon losses. The separation concept between components of natural gas is based on the difference in freezing points of individual components and their composition in the mixture. The overall process of cryogenic packed bed pipeline network consists of the initial cooling of each bed, the capture of individual component and regeneration of each bed. In previous studies, the process concept of cryogenic packed bed network was validated using experimentation but the optimization study was not carried out. The simulation results and thermodynamic behavior of the individual component in the mixture are included to further explain the process concept. The sensitivity study was carried out to investigate the effect of the temperature and the pressure of each packed bed. For sensitivity study, node-edge schemes were developed and discussed in details by changing operating conditions of packed beds. Based on the node-edge scheme analysis, the optimum values for both temperature and pressures were selected for maximum separation and minimum methane loss. The energy requirements for both dehydration and CO2 removal were calculated experimentally and compared with simulation results. For the simulation results, Aspen Hysys simulator was used along with Peng-Robinson fluid package. The energy requirements for both simulation and experimental results were calculated at atmospheric and high pressures. Both local and global optima were calculated using golden section search and depth-first strategy. The initial local optima result showed that the product purity can reach up to 77% methane, further optimization using depth-first strategy showed the product purity up to 94% with reduction of hydrocarbon losses from 39 to 16%. Highlights: Proposed cryogenic packed bed pipeline network for natural gas purification. Development of optimization strategy for cryogenic packed bed pipeline network. Effect of bed temperature and pressure in cryogenic packed bed on CO2 separation.